Penggunaan Model Pembelajaran CTL Bernuansa PAKEM Untuk Meningkatkan Hasil Belajar Mapel PJOK Siswa Kelas VI SD - Muhajirin Muhajirin (Universtas Negeri Makassar, 2022)
The problem in this study is the low learning outcomes in the PJOK subject achieved by students in each semester. The research method used is classroom action research (CAR), with implementation stages including: (1) planning, (2) implementation, (3) observation and evaluation, (4) reflection. The conclusion in this research is that the application of Contextual Teaching and Learning/CTL learning with PAKEM nuances can improve learning activities for Physical Education, Sports and Health for class VI UPT SDI Mallawa Region II, Barru District, Barru Regency..